Probabilistic slope stability analysis: a case study of Ain Bouzian landslide within North-East Algeria - Samir Ghedjati; Mohammed Lamara; Youcef Houmadi (Journal of Building Materials and Structures)
The aim of this study is to carry out a probabilistic analysis of slope stability within homogenous soil profile of Ain Bouzian landslides located north-east Algeria. This region suffers of many instability problems, which is aggravated during the construction of East-West motorway. The random variables for the soil considered in this study are the Young modulus E, cohesion C and friction angle φ. Stochastic soil properties values are used to evaluate the reliability and to assess sensitivity of the system, for two hydrological conditions, with and without water table within the soil mass. The deterministic model is based on Strength Reduction Method (SRM) analysis using the finite difference code FLAC3D.